PENGARUH TEKANAN AKADEMIK DAN DUKUNGAN SOSIAL TERHADAP KESEHATAN MENTAL SISWA (Survey Terhadap Siswa kelas VIII di SMP Yapi Al-Husaeni Kabupaten Bandung) - Auzra Rimba Fhasya; Fajar Eryanto Septiawan; Dedi Junaedi (PERFORMANCE: Jurnal Bisnis & Akuntansi, 2026)
Mental health in early adolescence is a crucial aspect influenced by various dynamics of the academic and social environment. This study aims to determine and analyze the effect of Academic Pressure (X1) and Social Support (X2) on Mental Health (Y) in eighth grade students at SMP YAPI Al-Husaeni, Bandung Regency. The research method used is quantitative with a correlational design. The population in this study amounted to 187 students, with a sample determined using the Slovin formula obtained as many as 127 respondents selected through a purposive sampling technique. Data collection was carried out using a questionnaire that had been tested for validity and reliability, while data analysis used multiple linear regression analysis with the help of IBM SPSS software. The results of the study showed that partially (t-test), Academic Pressure had a negative and significant effect on students' Mental Health, while Social Support had a positive and significant effect on students' Mental Health. Simultaneously (F-test), Academic Pressure and Social Support together had a significant effect on students' Mental Health with a contribution value (R Square) of 69.0%, while the remaining 31.0% was influenced by other variables outside this research model. Based on these results, schools are advised to balance academic demands with the provision of adaptive social support systems for students.